To find ∂f∂x{{\partial f}\over{\partial x}} and ∂f∂y{{\partial f}\over{\partial y}} for f(x,y)=(x2+xy)sin(y2+xy).f(x,y)=(x^{2}+xy)\sin(y^{2}+xy).
Solution. To calculate ∂f∂x\frac{\partial f}{\partial x}, think of yy as constant, say y=by=b. Then f(x,b)=(x2+bx)sin(bx+b2)f(x,b)=(x^{2}+bx)\sin(bx+b^{2}). So, by the product rule:
Similarly, setting x=ax=a: ∂f∂y=(ay+a2)′sin(y2+ay)+(ay+a2)(sin(y2+ay))′\frac{\partial f}{\partial y}=\,{(ay+a^{2})^{\prime}\sin(y^{2}+ay)+(ay+a^{2})(% \sin(y^{2}+ay))^{\prime}}